Tet1 Regulates Astrocyte Development and Cognition of Mice Through Modulating GluA1 - Xu, Weize; Zhang, Xicheng; Liang, Feng; Cao, Yuhang; Li, Ziyi; Qu, Wenzheng; Zhang, Jinyu; Bi, Yanhua; Sun, Chongran; Zhang, Jianmin; Sun, Binggui; Shu, Qiang; et al. (Frontiers in Cell and Developmental Biology, 2021)
Tet (Ten eleven translocation) mediated 5-hydroxymethylcytosine (5hmC) is highly enriched in the neuronal system and is involved in diverse biological processes and diseases. However, the function of 5hmC in astrocytes remains completely unknown. In the present study, we show that Tet1 deficiency alters astrocytes morphology and impairs neuronal function. Specific deletion of Tet1 in astrocytes impairs learning and memory ability of mice. Using 5hmC high-throughput DNA sequencing and RNA sequencing, we found the distribution feature of 5hmC in astrocytes and that Tet1 deficiency induces DNA hydroxymethylation regions (DhMRs) and alters gene expression. Mechanistically, we found that Tet1 deficiency leads to the abnormal Ca2+ signaling by regulating the expression of GluA1, which can be rescued by ectectopic expression of GluA1. Collectively, our findings suggest that Tet1 plays important functions by regulating astrocytes Ca2+ signaling.